2014
DOI: 10.1007/s00216-014-7702-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of five organophosphorus nerve agent metabolites in serum using hydrophilic interaction liquid chromatography and tandem mass spectrometry

Abstract: Although nerve agent use is prohibited, concerns remain for human exposure to nerve agents during decommissioning, research, and warfare. Exposure can be detected through the analysis of the hydrolysis products in urine as well as blood. An analytical method to detect exposure to five nerve agents, including VX, VR (Russian VX), GB (sarin), GD (soman) and GF (cyclosarin), through the analysis of the hydrolysis products, which are the primary metabolites, in serum has been developed and characterized. This meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…Concluding, verification of exposure to CWA plays an important role in the way that unambiguous confirmation of an alleged use of banned substances by military or terrorist forces may have far‐reaching political and legal impact. However, direct detection of CWA in vivo is quite difficult due to rapid clearance from the circulation and structural changes in the course of biotransformation processes . Therefore, current efforts are focused on identification of adducts between CWA and endogenous target molecules (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Concluding, verification of exposure to CWA plays an important role in the way that unambiguous confirmation of an alleged use of banned substances by military or terrorist forces may have far‐reaching political and legal impact. However, direct detection of CWA in vivo is quite difficult due to rapid clearance from the circulation and structural changes in the course of biotransformation processes . Therefore, current efforts are focused on identification of adducts between CWA and endogenous target molecules (e.g.…”
mentioning
confidence: 99%
“…However, direct detection of CWA in vivo is quite difficult due to rapid clearance from the circulation and structural changes in the course of biotransformation processes. [2,[4][5][6] Therefore, current efforts are focused on identification of adducts between CWA and endogenous target molecules (e.g. proteins), as these biomarkers are still detectable days or even weeks after exposure.…”
mentioning
confidence: 99%
“…OPNA metabolites were extracted from the dried sample using methanol coupled with a small volume of aqueous internal standard; this combination achieved ~100% recovery of all analytes from the DBS with a short incubation period at room temperature. The direct extraction of OPNA metabolites from DBS resulted in minimal matrix effects (−2.27–2.24%), eliminating the need for additional sample preparation such as solid phase extraction as was necessary for the wet whole blood, plasma, and serum samples 11, 17 . Precision ranged from 6.17–14.2% and accuracy ranged from 93.6–111% for two quality control samples at 30 and 250 ng/mL assessed over a period of 66 days, with a maximum of two analyses per day.…”
Section: Data and Resultsmentioning
confidence: 99%
“…(Black, 2010) Nerve agent metabolites can be detected in blood and urine; however, these metabolites are excreted from the body within two weeks following exposure. (Hamelin et al, 2014, Mawhinney et al, 2007, Riches et al, 2005) OPNAs also form protein adducts which can provide a previously reported two to three months for retrospective detection. (Black and Read, 2013) The Ellman activity assay has been used to determine OPNA exposure by measuring cholinesterase activity but lacks the specificity to distinguish OPNAs from organophosphorus pesticides or other compounds capable of inhibiting cholinesterases.…”
Section: Introductionmentioning
confidence: 83%